2005
DOI: 10.1007/s00417-005-1142-9
|View full text |Cite
|
Sign up to set email alerts
|

Deviations between transpalpebral tonometry using TGDc-01 and Goldmann applanation tonometry depending on the IOP level

Abstract: TGDc-01-based tonometry demonstrated an increasing underestimation of IOP with increasing IOP levels when compared with the current standard method of Goldmann applanation tonometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
(20 reference statements)
0
11
0
1
Order By: Relevance
“…Twenty studies 124,125,127,133,[136][137][138]158,162,164,168,172,[176][177][178]191,198,205,207,208 enrolling 1509 participants (2091 eyes) compared transpalpebral tonometer with GAT. Figure 45 summarises the quality assessment for these studies.…”
Section: Transpalpebral Tonometermentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies 124,125,127,133,[136][137][138]158,162,164,168,172,[176][177][178]191,198,205,207,208 enrolling 1509 participants (2091 eyes) compared transpalpebral tonometer with GAT. Figure 45 summarises the quality assessment for these studies.…”
Section: Transpalpebral Tonometermentioning
confidence: 99%
“…In total, 10 studies 124,127,137,138,168,176,178,191,198,208 (50%) reported individual measures taken within 1 hour. In 12 studies (60%) the same clinical data were available for interpretation as would be available in clinical practice 124,127,133,137,138,158,162,168,172,177,205,207 and it was reported that the examiner(s) were masked to the results. 124,125,158,162,168,172,[176][177][178]205,207,208 In seven studies 125,127,172,177,178,205,208 (35%) the tonometers used were calibrated.…”
Section: Transpalpebral Tonometermentioning
confidence: 99%
“…Troost et al [15] demonstrated that there was an increasing underestimation of the IOP by TGDc-01 tonometry compared with GAT with increasing IOP levels. They did not recommend the transpalpebral tonometry device, TGDc-01, as a substitute for GAT, at least when its use in patients with increased IOPs ≥20 mmHg was intended.…”
Section: Discussionmentioning
confidence: 98%
“…When the tip of the tonometer touched the eyelid, the measurement (falling of the rod) was automatically started [2]. In this study, GAT measurements were performed after installation of Alcain eye drops (Alcon Pharmaceuticals Inc., Puurs, Belgium) and positioning the scale of the tonometer at 10 mmHg [3,15,16].…”
Section: Methodsmentioning
confidence: 99%
“…Troost et al [7,10] demonstrated that there was an increasing underestimation of the IOP by TGDc-01 tonometry compared with the GAT with increasing IOP levels and concluded that the device may not be a substitute for the GAT, at least when its use in patients with increased IOPs ≥20 mm Hg was intended. They, however, recommended that TGDc-01 was a better choice for tonometry in patients with corneal pathology or in awake children than palpation of IOP, at least in normotensive subjects.…”
Section: Discussionmentioning
confidence: 99%